Adoption of E-Wallets in Timor-Leste: An Extended UTAUT Approach - Gusmao, Mazarino Neil Araujo Pires Leite; Hidayanto, Achmad Nizar; Isal, Yugo Kartono; Wibowo, Wahyu Catur (Jurnal Informatika Ekonomi Bisnis, 2025)
This study investigates the factors influencing the adoption of e-wallets in Timor-Leste using an extended Unified Theory of Acceptance and Use of Technology framework. Incorporating context-specific variables digital literacy, trust, inertia, merchant availability, and socialization and campaign the research employs a quantitative approach with data collected from 338 respondents through structured questionnaires. Analysis using Partial Least Squares Structural Equation Modeling reveals that four variables performance expectancy (β = 0.325), digital literacy (β = 0.161), socialization and campaign (β = 0.117), and trust (β = 0.321) significantly influence intention to use e-wallets. Trust emerged as the most influential factor, underscoring the need for secure, transparent systems to encourage adoption. Surprisingly, effort expectancy, social influence, digital infrastructure, merchant availability, and inertia were found to be non-significant. The model explains 77.1% of the variance in intention to use, with a high predictive relevance (Q² = 0.753). These findings suggest that user adoption in low-infrastructure contexts depends more on perceived trust and technological competence than on ease of use or peer influence. The results provide strategic insights for policymakers, service providers, and development actors aiming to promote financial inclusion through digital services in emerging economies like Timor-Leste.